The Success of E-Filing Adoption during COVID 19 Pandemic: The Role of Collaborative Quality, User Intention, and User Satisfaction - Atika Jauharia Hatta Hambali (Journal of Economics, Business, and Accountancy Ventura, 2020)
This study aims to test the successful use of e-filing information systems in tax return reporting, which is more widely used by taxpayers during the COVID 19 pandemic to report tax return than before. Data were obtained by a survey using a questionnaire with taxpayers as respondents. The purposive sampling method was used to collect data, with the final results of 93 respondents. The partial least square results for data processing reflect that service quality and collaboration quality are determinants of e-filing user satisfaction, while user intentions only influenced by collaboration quality. Overall, this study can support the model that the success rate of e-filing is determined by user intentions and user satisfaction, which is shown by the net benefits generated from using e-filing systems. This study suggests that the Di-rectorate General of Taxation needs to increase user satisfaction and user intention mainly through collaborative quality.